Synergy of Public Relations and Hospital Management for Healthcare Delivery: A Study of Selected Hospitals in Delta State - Ivwighren, Hannah Emuobosa; Egbi, Toju (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
This study explores the relationship between public relations (PR) strategies and hospital administration in Delta State, Nigeria. Using a mixed-methods approach, the study investigates how PR tactics are integrated into daily operations, their impact on healthcare services, stakeholder involvement, patient satisfaction, and overall perception of healthcare facilities. The sample consisted of 400 patients and staff from three selected hospitals. Data was collected through a questionnaire and interviews with hospital executives, public relations specialists, and key stakeholders. Interviews with hospital executives, public relations specialists, and key stakeholders on managing the hospitals' reputation and public image are used to collect qualitative data. Findings show that PR strategies are significant for communicating hospital policies and can be easily incorporated into daily practice without disrupting operations. It was also revealed that clear communication through PR practices can translate to better patient expectations and understanding, providing a better experience. The study recommends that feedback mechanisms be applied to patients and staff to make it easy for hospitals to determine challenges and the impact of PR strategies and even integrate improvements. The study is significant to healthcare administration and public relations, and it will show how these two industries might work together to enhance healthcare delivery and patient happiness for healthcare administrators in Delta State.